Aneurysmal subarachnoid hemorrhage associated with small aneurysms in smokers and women: A retrospective analysis (2019)
Background Previous studies have shown low rupture rates for small aneurysms (<10 mm), suggesting that the risk of treatment could exceed the benefits. However, evidence has changed, showing crescent rates of aneurysmal subarachnoid hemorrhage (aSAH) associated with small aneurysms. We report trends in size, localization, clinical characteristics, and outcomes of intracranial aneurysms (IAs). Methods In this retrospective study, a total of 200 clinical histories of patients diagnosed with IAs over an 8-year period were analyzed. Variables considered included age, sex, tobacco consumption, morphological characteristics of the aneurysm, complications, vasospasm, and mortality. Qualitative variables were assessed by measurements of absolute and relative frequency. Smoking behavior, aneurysm size, and aneurysm rupture (AR) were compared using 1-way analysis of variance. Categorical variables were analyzed using Pearson's χ2 test. Results The average age at presentation was 58 years. The average size of ruptured aneurysms in the general group was 2.5–7.5 mm, and AR was most common in women (76%) and in patients age 50–60 years (33%). The rate of vasospasm was 19%, and mortality was 37%. Smokers composed 32% of the cohort. Heavy smokers had a 57% rate of aSAH, with an average size of rupture of 5 mm. The most common location of aneurysms and AR was the AComA (33%). Conclusions Our results suggest increasing AR rates in aneurysms smaller than 10 mm. This trend is seen especially in individuals with heavy tobacco consumption and in women of perimenopausal age. Our findings show a tendency of AR in accordance with previous results and are expected to serve as basis for further research on aneurysm management.